Distribución geográfica y factores asociados a tuberculosis MDR y XDR en población pediátrica de un hospital de la Amazonía Peruana, 2024-2025 - Vargas Atauje, Keever Fritz (2025)
Introduction: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which mainly affects the lungs, although it can compromise other organs. Its multidrug-resistant (MDR) form, characterized by resistance to isoniazid and rifampicin, and its extensively drug-resistant (XDR) form, which exhibits additional resistance to fluoroquinolones and second-line drugs, represent a growing threat to public health. These variants make treatment difficult and increase morbidity and mortality, especially in the pediatric population of vulnerable regions such as the Peruvian Amazon, where socioeconomic and geographic factors limit timely access to diagnosis and treatment. Objective: To determine the geographical distribution and factors associated with MDR and XDR tuberculosis in the pediatric population of a hospital in the Peruvian Amazon, 2024-2025. Method: The study was designed as observational, analytical, prospective, and cross-sectional. Population: The target population consisted of 35 pediatric patients with MDR and XDR tuberculosis and a sample of 28 pediatric patients with MDR and XDR tuberculosis from a hospital in the Peruvian Amazon, 2024-2025. Results: Data collection was planned using structured forms applied to hospitalized patients and those under observation in the pediatric ward, with prior authorization from the Ethics Committee. The data would have been organized in an Excel database and processed using SPSS v26.0 software. The statistical analysis would include descriptive measures and the application of Fisher's exact test to evaluate associations between qualitative variables, considering a p value < 0.05 as significant. Conclusion: MDR and XDR tuberculosis in the pediatric population is a complex expression of the disease, where bacterial resistance to essential drugs prolongs the duration of treatment and hinders its effectiveness, especially in contexts with geographical barriers and limited access to specialized services.